The Effect Of Green Banking On Company Value With Corporate Social Responsibility As A Moderating Variable - Dana, Agus Mulyawan; Sunarto , Sunarto (Amkop Management Accounting Review (AMAR), 2025)
Rapid and uncontrolled economic changes in various industries have damaged the natural environment. The financial industry remains committed to ensuring environmental sustainability. This study aims to determine the effect of Green Banking on the Value of Banking Companies listed on the Indonesia Stock Exchange for the 2019-2023 period. And also to see the role of Corporate Social Responsibility (CSR) as a moderator in influencing Green Banking on Company Value. The author uses a quantitative method with documentation data collection techniques and literature studies. The results obtained are that Green Banking has a negative and significant effect on company value and Corporate Social Responsibility has a positive and significant effect on company value and Corporate Social Responsibility is able to moderate the effect of Green Banking on company value with a weakening relationship